The First Precariat?. (18th April 2017) - Fink, Leon
Abstract : The transformation of global capitalism, labor, and class relations in our own day is having a marked effect on how we study those subjects historically. Yet, as happens repeatedly in our historical discipline, insights gained from the juxtaposition and recognition of deep structural affinities between the present and the past also carry the risk of a distorted mirror effect. What questions we carry to the past and what lessons we, in turn, extract from it must be handled with care. As couriers between worlds of time as well as space, our work as historians inevitably reflects the ignorance as well as intelligence attending the message (as well as the messenger) of the given moment. With these caveats in mind, I want to explore the link between today's global crisis in worker welfare—perhaps most commonly summoned up by the twinned terms "neoliberalism" and the "precariat"—and a new historical preoccupation with coerced laborers of the past. With due deference to the aims of this collection, I will concentrate on the connection between the coolie question, as it developed in the nineteenth and early twentieth centuries, with the plight (and possible strategies) of low-wage global workers today.